German Citizens’ Perception of Fattening Pig Husbandry—Evidence from a Mixed Methods Approach - Inken Christoph-Schulz; Anja-Karolina Rovers (Agriculture, 2020)
Pig production in Germany is experiencing an increasing discrepancy between social attitudes, wishes and the reality. To investigate the actual perception and knowledge of fattening pig husbandry by German citizens, a mixed methods approach was carried out. First, six focus group discussions were conducted. Content analysis showed that space availability, fresh air supply and flooring type are particularly relevant in citizens’ perception, whereas surgical interventions on the animal are perceived less. Furthermore, preventive use of antibiotics is seen critically by the participants. Based on these results, an online survey with 399 respondents was conducted to quantify the results. Findings from the focus groups were confirmed: Lack of space as well as the perceived precautionary use of medication were seen most critically. Results are influenced by if respondents have visited a farm before, the dietary behavior and sex.